The perils of PROMs: question 5 of the Oxford Hip Score is ambiguous to 10% of English-speaking patients: a survey of 135 patients. Issue 3 (May 2019) - Péchon, Pierre H M; Butler, Katherine; Murphy, George; Singer, Gian C
Introduction: The Oxford Hip Score (OHS) is a commonly used patient-reported outcome measure (PROM), comprising 12 questions. We present the incidental finding that one of the 12 questions is ambiguous. Materials and methods: As part of a 10-year follow-up of patients treated with hip resurfacing the OHS was posted to 148 patients; 135 (91%) replied. Scores were read by 2 orthopaedic surgery trainees and entered into a database. It was noted that Question 5 was frequently mis-interpreted. Results: Thirteen patients' questionnaires (10%) showed the same inconsistency: question 5 was scored as 0 points but the other 11 questions were scored as either 3 or 4 in 97% of cases. The ethnic group of all 13 patients was recorded in hospital data as being White-British. Conclusion: Question 5 of the OHS is ambiguous to 10% of native English-speakers. These patients rated their hip function highly, as reflected by the fact that 97% of the questions other than question 5 scored 3 or 4, indeed 87% of them scored 4. We hypothesise that the wording of the zero score option "Not at all" is being mis-interpreted as a response indicating that the patient does not suffer any pain at all. The effect is an error of 4 points out of 48 (8%); this may under-estimate the patient's hip score. Surgeons are under great scrutiny to prove efficacy of surgical interventions; this is often provided by PROMs. We should strive to formulate the most accurate, reproducible and least ambiguous PROMs questionnaires.